Analysis of Diarrheal Disease Transmission in Bandung City Using the SIS Mathematical Model. - Ulfa, Rezky Maya; Shaumi, Nurina Fadlila; Nuraini, Nuning (Universitas Negeri Makassar, 2025)
Diarrhea remains a public health issue in developing countries around the world. It is categorized as an environmentally-based disease and occurs in nearly all geographic regions globally. The purpose of this study is to apply mathematical modeling of the spread of diarrhea in Bandung City using the SIS model, then to model the relationship between the number of rivers and the quantity of E. coli in each district in Bandung City with the number of diarrhea cases, as well as to analyze the influence of river presence and E. coli quantity in each district on the number of diarrhea cases in Bandung City. The model development began by creating a flow diagram of the spread of diarrhea using the SIS model. The results revealed an equilibrium point, specifically the endemic equilibrium point. The basic reproduction ratio in each district showed values closely aligned with mortality rates, indicating that mortality rates from the disease could serve as a useful indicator for predicting transmission rates and the impact of diarrhea within the population. The higher the mortality rate, the lower the likelihood of disease transmission, and vice versa.